Organização curricular da Educação Física no ensino fundamental em Catalão-GO: análise a partir do discurso dos professores - ARRUDA, Leomar Cardoso (2014)
This study aims to understand the perspective of Teachers of Physical Education and the Pedagogical Coordination of Municipal Education Department, the organization of the curriculum of elementary school. To meet the goal we reflect on the relationship between Education, Physical Education and Curriculum, until we reach the point of this discussion, namely, the organization of content in physical education classes (PE) from first to ninth grade. The study is qualitative in nature and the information was obtained through interviews with 08 teachers of Physical Education in Elementary Education from the Municipal Education (EMS) and effective teaching practice and 01 educational coordinator of the EMS in office in 2013 in city of Catalao-GO. Data collection was done in two phases: the study of the document entitled: "experimental Curriculum Reference Physical Education for Elementary School" and the analysis of the interviews by drafting proposed categories by content analysis (Minayo , 2002). The proposed curriculum established by SME presents a diversity of content organized into two-month periods, which recur throughout the series. Seven subjects (77.7%) are unaware of the research proposed curriculum for PE implemented by EMS Catalao. For 62.5% of teachers PE reality student / profile is the main factor that defines the choice of content. The lack of pedagogical support coordination of school units and EMS, as the selection and organization of content to be taught, is present in the speeches of 100% of PE teachers. Teachers systematize content throughout the year by marking periods, and team sports main content. Four teachers understand that the content should be organized according to the series of first and second phase of elementary school, three comprise the organization of the contents should be the same in all grades and one teacher defends what is established by the curriculum. For seven teachers of PE are taught and organized content (what you do) do not converge with the content they should teach (what is said) in each series. The lack of material appears in the speech of 87.5% of the subjects in this study as the main difficulty for the teaching of content, followed by inadequate physical space and disinterest / student resistance, corresponding to 50% each. For seven subjects of this investigation the creation of collective spaces for discussions on curriculum organization appears as the main aspiration 9 of the group. Six teachers yearn for the creation of a curriculum proposal for the municipal PE Education. The conclusion to this study that there is a mismatch between what is established / proposed by EMS with what is materialized in daily physical education teacher, as all teachers in this study have a different curriculum organization indicated in the tender implemented by the municipal Catalao Education for Physical Education.